Socio-Economic Characteristics of Residents in Correlation to Groundwater Source in Ikenne Local Government Area, Ogun State, Nigeria - Adewunmi, A. A.; Akinpelu, O. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The study examines the residents’ socio-economic characteristics as correlates of groundwater source in Ikenne Local Government Area, Ogun State, Nigeria. The objectives addressed in this study are analysis of the socio-economic characteristics of the residents; sources of groundwater; and relationship between residents’ socio-economic attributes and groundwater source in the study area. A total of two hundred and seventy-two (272) respondents across all the six political wards of Iperu and Ilisan, were administered using questionnaires. Data collected were analysed using frequency distribution, percentage, ANOVA (it is used to establish if there is significance different between variable), Correlation and Regression. The study revealed that there is no significant difference in socioeconomic background of the residents (p > 0.05) except for educational attainment. It was found that correlation exists between groundwater source and marital status, education, income and occupation with exception of gender. Regression results established that 82 % of variability in groundwater source is predicted by residents’ socioeconomic characteristics. It could be concluded that socioeconomic background of the residents significantly influences their source of groundwater. It is therefore imperative that governments at all levels need to come up with policies and programmes that will enhance peoples’ socioeconomic status, thereby enhancing their ability to provide an improved water source.